Strategi Guru Mengelola Kelas dalam Meningkatkan Keaktifan Belajar Siswa Kelas VIII pada Mata Pelajaran Bahasa Indonesia di SMP Islam Integral Luqman Al-Hakim Batam - Juni Mahanis; Syahwani Syahwani (TADRIBUNA, 2022)
This thesis discusses the teacher’s strategy for managing the classroom in increasing the learning activities of class VIII students in Indonesian subjects at the Luqman Al-Hakim Batam Integral Islamic Junior High School. This type of research is qualitative research, data collection is carried out using the methods of observasion, interviews, and documentation. This study found that the implementation of the teacher’s strategy in managing the classroom in increasing student learning activity was quite good, namely with activities that could motivate students to learn by arranging student seats, clean and tidy classroom. Meanwhile, the obstacles faced by teachers are the condition of students who are sleepy during class hours and the lask of adequate facilities and infrastructure such as books, learning tools and the state of student desks and chairs. The result of this study suggest that teachers are able to be examples and role models for students to achieve their goals, and always provide motivation to students..